DETECTION OF WEED IN AGRICULTURAL FILED USING IMAGE PROCESSING (International Journal of Food and Nutritional Sciences, 2022)
Agriculture is a fundamental source ofnourishment for humanity on this planet. In thepresent day, as a result of the increasingpopulation, there is a need for agriculture tohave a higher level of productivity in order tofulfill the needs. In ancient times, people usedtraditional techniques to enhance output, such asusing cow dung as a natural fertilizer inagricultural areas. This led to a significant boostin output that was sufficient to fulfill thepopulation's demands. However, subsequentindividuals contemplated the idea of maximizingearnings by increasing the yield. Thus, a revoltknown as the "Green Revolution" emerged.Subsequently, the use of lethal toxins asherbicides has escalated significantly over thistime frame. While our efforts to increaseproduction have been successful, we haveoverlooked the detrimental impact on theenvironment, which raises concerns about ourability to sustain ourselves on this magnificentplanet. In this effort, we have used techniques tominimize herbicide consumption by selectivelyspraying them only in regions where weeds arepresent. This study presents the implementationof image processing techniques using MATLABto identify and locate regions of weed growth ina picture captured from agricultural fields. Withthe global population expanding and availableland and natural resources diminishing, expertsare paying greater attention to precisionagriculture. Image processing methodologiesmay be used to address this issue.Keywords: Image processing, Agriculture,Color segmentation .